Hubungan Konsep Diri Profesional dengan Kesiapan Profesional pada Mahasiswa Profesi Ners Generasi Z - Siti Amalia Galuh Putri (Fakultas Keperawatan, 2026)
Introduction: Suboptimal professional preparedness among Generation Z nursing students remains a significant challenge in preparing graduates to meet the demands of contemporary nursing practice. Evidence regarding the relationship between professional self-concept and professional preparedness among Generation Z nursing students remains limited. Therefore, this study aimed to examine the relationship between professional self-concept and professional preparedness among Generation Z nursing students. Methods: This quantitative correlational study employed a cross-sectional design. The sample consisted of 371 Generation Z nursing professional program students, determined using the Slovin formula and selected through purposive sampling. Data were collected online using the Professional Self-Concept of Nurses Instrument (PSCNI) and the Perception of Professional Readiness in Nursing Scale (PPRNS). Descriptive statistics and the Spearman Rank correlation test were used for data analysis. Results: Most respondents had high professional self-concept (51.5%) and high professional readiness (50.1%). The communication dimension had the highest proportion of respondents with high professional self-concept (59.6%), while the professional qualification dimension had the highest proportion of respondents with high professional readiness (70.1%). Spearman Rank analysis demonstrated a significant positive correlation between professional self-concept and professional readiness (p = 0.001; r = 0.685), indicating a strong positive relationship. Conclusion: Generation Z nursing professional program students with higher levels of professional self-concept tended to exhibit higher levels of professional preparedness, suggesting that professional self-concept should be considered as one of the important factors in preparing students for professional nursing practice. Further research is warranted to investigate other variables and factors associated with professional preparedness among generation Z nursing professional program students.
Finalisasi Rudy K
Keywords: generation Z; nursing professional program students; professional readiness; professional self-concept